Five-year review of corticosteroid duration and complications in the management of immune checkpoint inhibitor-related diarrhoea and colitis in advanced melanoma. Issue 4 (8th July 2020) - Favara, David M; Spain, Lavinia; Au, Lewis; Clark, James; Daniels, Ella; Diem, Stefan; Chauhan, Dharmisha; Turajlic, Samra; Powell, Nick; Larkin, James M; Yousaf, Nadia
Abstract : Background: Immune-related diarrhoea/colitis (ir-D/C) is a common adverse event of immune checkpoint inhibitor (ICI) therapy. Guidelines recommend corticosteroid (CS) treatment; however, the average treatment duration for ir-D/C remains poorly defined. Methods: All advanced melanoma patients treated with ICI therapy at the Royal Marsden Hospital between 2011 and 2016 were reviewed to identify ir-D/C cases alongside clinical variables. Results: 117 any-grade ir-D/C episodes occurred in 109 (21%) patients out of a total of 519 patients treated (ipilimumab=77 episodes, anti-PD1=17 (nivolumab or pembrolizumab), ipilimumab and nivolumab=23 (ipi+nivo)) (seven patients had ir-D/C more than once on different lines of treatment) and >/=grade 3 ir-D/C occurred most frequently (63/519 patients (12%) vs 29/519 (5%) grade 1, and 25/519 (5%) grade 2). Median onset (days) of all-grade ir-D/C after starting ICI therapy was 41 for ipilimumab (IQR 24 to 59, n=77), 91 for anti-PD1 (IQR 46 to 355, n=17) and 45 for ipi+nivo (IQR 24 to 67, n=23). In 71/117 (61%) patients, ir-D/C episodes were treated with CS (17% grade 2; 79% grade 3/4): 54 being steroid-responsive; 17 being steroid-refractory and received additional anti-tumor necrosis factor (TNF) treatment. Median grade 3 ir-D/C CS duration was similar across treatments, averaging 58 days. Median overall CS duration (days) was longer in the grade 3/4 D/C steroid-refractory group (94 vs 45 days). Infection developed in 11/71 (15%) CS recipients and in 6/17 (35%) anti-TNF recipients. In 65/117 (55%) patients, ir-D/C episodes were investigated with flexible sigmoidoscopy. Of these patients, 38/65 (58%) had macroscopic colitis and 12/65 (18%) had microscopic colitis. The steroid-refractory group had more macroscopic changes, 13/17 (76%), than the steroid-responsive group, 22/41 (54%). Conclusion: Rates of grade 3 ir-D/C were higher than reported in clinical trials. The 58-day median duration of CS therapy for grade 3 ir-D/C places a significant number of patients at risk of complications. We demonstrate that microscopic colitis is an important subgroup, advocating biopsies in ir-D/C even with macroscopically normal bowel.